Semi-transparent perovskite solar cells for tandems with silicon and CIGS. Issue 3 (12th January 2015) - Bailie, Colin D.; Christoforo, M. Greyson; Mailoa, Jonathan P.; Bowring, Andrea R.; Unger, Eva L.; Nguyen, William H.; Burschka, Julian; Pellet, Norman; Lee, Jungwoo Z.; Grätzel, Michael; Noufi, Rommel; Buonassisi, Tonio; et al.
Abstract : Semi-transparent perovskite solar cells with silver nanowires are stacked on CIGS and Si to achieve solid-state polycrystalline tandems with efficiency improvement. Abstract : A promising approach for upgrading the performance of an established low-bandgap solar technology without adding much cost is to deposit a high bandgap polycrystalline semiconductor on top to make a tandem solar cell. We use a transparent silver nanowire electrode on perovskite solar cells to achieve a semi-transparent device. We place the semi-transparent cell in a mechanically-stacked tandem configuration onto copper indium gallium diselenide (CIGS) and low-quality multicrystalline silicon (Si) to achieve solid-state polycrystalline tandem solar cells with a net improvement in efficiency over the bottom cell alone. This work paves the way for integrating perovskites into a low-cost and high-efficiency (>25%) tandem cell.